More frequent consecutive extreme precipitation in the dry regions of China - Huang, Lirong; Du, Haibo; Dang, Yongcai; He, Hong S.; Na, Risu; Wu, Zhengfang (International journal of climatology, 2022)
Precipitation extremes occurring on consecutive days may be of crucial importance for the formation of extensive and long‐lasting flooding. Changes in such consecutive extreme precipitation (CEP) events between different regions (i.e., dry and wet regions) still remain unclear in China, which may result in different impacts on human livelihoods and ecosystems. Here, the changes in CEP frequency between dry and wet regions of China were studied by utilizing an observation‐based gridded precipitation dataset. We further determined the driving factors of the changes in CEP frequency by separating the effects of precipitation intensification and temporal clustering of daily extreme precipitation. Our results showed that the CEP frequency in dry regions increased faster (9.73%·decade−1) compared with wet regions (1.14%·decade−1) during the last ~60 years. The increasing precipitation intensity primarily (over 90%) resulted in the increases of CEP events. However, changes in the temporal clustering of daily extreme precipitation can benefit the effects of the changes in precipitation intensity in dry regions but can reverse these effects in wet regions. In dry regions, the regression relationship of precipitation intensity and temperature (7.38%·°C−1) was stronger than that in wet regions (3.44%·°C−1), suggesting that the same magnitude of warming would cause greater precipitation intensity and consequently cause more frequent CEP events in dry regions. Therefore, as the intensification of precipitation and the increasing temporal clustering of daily extreme precipitation, more CEP events may increase the flooding risk in dry regions over China with a stronger warming signal. The consecutive extreme precipitation is more frequent in dry regions of China. Increased precipitation intensity and temporal clustering of daily extreme precipitation drivers the change of consecutive extreme precipitation. More consecutive extreme precipitation in dry regions of China with global warming.